Pharmacological treatment and impairment of pulmonary function in patients with type 2 diabetes: A cross-sectional study (2016)
Introduction: There is no clear relationship between type 2 diabetes mellitus and lung function decline; it is also unclear whether the type of treatment can modify spirometric variables and levels of inflammatory biomarkers. Objectives: To compare pulmonary function in patients with type 2 diabetes treated with an insulin-sensitizing agent (metformin) and in those treated with secretagogues, as well as combined with insulin, and to evaluate differences in inflammatory biomarkers between treatment groups. Material and methods: We conducted a cross-sectional analytic study in 196 diabetic patients with type 2 diabetic mellitus. Spirometric variables and levels of inflammatory biomarkers (ferritin, fibrinogen, C-reactive protein, interleukin 6, tumor necrosis factor-alpha), were obtained. Residual values (observed minus expected) for forced vital capacity and for forced expiratory volume were calculated and compared between treatment types. Differences in median levels of biomarkers were also compared. Results: After adjustment by known determinants of lung function, and by the control and duration of type 2 diabetes, patients treated with the insulin-sensitizing agent had statistically significant lower differences against expected values for forced vital capacity compared with secretagogues (-212.1 ml vs 270.2 ml, p=0.039), as well as for forced expiratory volume, but without statistical significance (-133.2 mL vs -174.8 mL, p>0.05). In the group of patients treated with the insulin-sensitizing agent, ferritin and tumor necrosis factor-alpha levels were lower (p less than 0.01). Conclusion: This study supports the hypothesis that insulin-sensitizing agents appear to be associated with less deterioration of lung function and less systemic inflammation in type 2 diabetes. The present study serves to formulate new hypothesis and research projects.